Pengaruh kombinasi HIIT berenang dan ekstrak Centella asiatica terhadap kecemasan dan memori pada tikus wistar - Qonita Sari Bustomi; Rahma Fithriyatun Nisa; Nisrina Nabila Gunawan; Marvel Lumingkewas; Fairuz Tsuraya Ramadhani; Nisa Kartika Komara (Poltekkes Kemenkes Aceh, 2024)
Background: Neurodegenerative diseases are associated with progressive memory loss and can lead to neuronal cell damage. One consequence of neuronal cell damage is the decline in short-term memory. Changes in short-term memory can be caused by increased levels of anxiety and depression in the elderly, potentially leading to dementia. The antioxidant substances in Centella asiatica and the effects of physical exercise have potential in preventing the decline in anxiety levels and short-term memory.Objectives: to determine the effects of combination of swimming HIIT and Centella asiatica oil extract on anxiety and short-term memory in adult male Wistar rats.Methods: The research method used was a pre-test post-test design with a control group on male Wistar rats. The study was conducted in the Laboratory of the Faculty of Medicine, University of Palangka Raya, from April to July 2024. The sample consisted of 24 rats divided into 4 groups: Control (K1), treatment of swimming HIIT (K2), administration of Centella asiatica Oil Extract (K2), and the combination of swimming HIIT with Centella asiatica Oil (K4). Data analysis was performed using One Way ANOVA, followed by Post Hoc Test with a 95% confidence interval.Results: There is a significant difference in anxiety levels and short-term memory between treatment groups (p= <0,001). Based on these results, the group with the best outcome is the group that received the combination treatment of swimming HIIT and Centella asiatica oil, as evidenced by a significant difference between the combination group and the other groups (p = <0,001).Conclusion: The combination treatment of swimming HIIT and Centella asiatica oil has the best potential for reducing anxiety levels and improving short-term memory in adult male Wistar rats.